2010
DOI: 10.1016/j.jvs.2010.06.088
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Revascularization Improves Heart Failure Control in Patients with Atherosclerotic Renal Artery Stenosis

Abstract: about the value of raising HDL-C. There is therefore also a need to reliably characterize the relationship between HDL-C and vascular risk, especially at the high HDL-C levels (N Engl J Med 2007;357:2109-22). Given uncertainties of the relationship between LDL-C and HDL-C levels and the various manifestations of vascular disease, as well as the uncertainties of the roll of proatherogenic lipoproteins in various types of vascular disease, the authors sought to produce reliable estimates of the association of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…Outcomes in HF and BP control were improved by revascularization compared with outcomes of patients who underwent medical management, but mortality was not affected. 663 Investigators from the ASPIRE II (renal Artery Stenting After Unsuccessful Balloon Angioplasty) study analyzed safety and durability of renal stenting after suboptimal or failed renal artery BA in patients, average age 69Ϯ9.9 years. Stenting was immediately successful in 80.2% lesions treated, and at 9 months, the restenosis rate was 17.4%.…”
Section: Percutaneous Renal Artery Stentingmentioning
confidence: 99%
“…Outcomes in HF and BP control were improved by revascularization compared with outcomes of patients who underwent medical management, but mortality was not affected. 663 Investigators from the ASPIRE II (renal Artery Stenting After Unsuccessful Balloon Angioplasty) study analyzed safety and durability of renal stenting after suboptimal or failed renal artery BA in patients, average age 69Ϯ9.9 years. Stenting was immediately successful in 80.2% lesions treated, and at 9 months, the restenosis rate was 17.4%.…”
Section: Percutaneous Renal Artery Stentingmentioning
confidence: 99%
“…One study in 163 consecutive patients who underwent percutaneous transluminal renal angioplasty for atherosclerotic RAS, reported that heart failure was present in one-third of the patients, and renal revascularization had resulted in improved heart failure control and a reduction in hospitalizations. 16) In contrast, few reports have described the efficacy of renal revascularization in FMD patients with congestive heart failure. In the present case, successful surgical revascularization was achieved without major periprocedural complications; blood pressure was well controlled during the 33 months of follow-up with improved BNP serum concentration and LV diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure, either flash pulmonary edema (FPE) or CHF, is a well-recognized clinical presentation for ARVD. Although the hearts of patients with FPE have not been subject to systematic study, Kane et al did examine the hearts of ARVD patients being referred for renal revascularization at the Mayo clinic (7), dividing patients into those with and without clinical heart failure; mean LVM was greater in those with CHF (LVM index 130±34 vs. 112±31 g/m 2 ). Randomized controlled trials comparing the addition of percutaneous renal artery revascularization to optimal medical therapy in ARVD have, at best, shown only minor and inconsistent benefits in blood pressure control (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%